Criticism Of Social Injustice Reflected In Victor Hugo's Les Miserables(1862):A Sociological Approach - Ros, Febrya Isyana; , Dr. M. Thoyibi, M.S (2017)
ABSTRACT This study is about "Criticism of Social Injustice Reflected in Victor Hugo's Les Miserables"(1862) using Sociological Approach. The objectives of the study are to identify the characteristics of Social Injustice using Sociological Approach, to describe the causes of Social Injustice which is illustrated in Victor Hugo's Les Miserables, To describe the impact of Social Injustice towards the main character in the novel Les Miserables.This research uses qualitative research.The primary data of this research is Les Miserables by Viktor Hugo, while the secondary data of this research is other sources related to the study, such as: virtual sources and other printed materials that support this research. The researcher draws three conclusions in this research. First, social injustice is characterized by such qualities as Elitism is Efficient, Exclusion is Necessary, Prejudice is Natural, Greed is Good, and Despair is Inevitable.Second, the causes of social injustice are depicted mainly through the plot concluding that it happens because of Poverty, Crime and Criminal Injustice, the Changing Family, School and Education, Work and Economy, and Health and Healthy Care. Those make social injustice happen toward the society. Third, the effects of social injustice can be concluded namely:Increased Poverty, Overcrowding, Famine, Species Loss, Weather Extreme, Acute and Chronic Medical Illness, and War and Human Right Abuses. Keywords: Social Injustice, Les Miserable, Sociology of literature.